Rad51 protects nascent DNA from Mre11-dependent degradation and promotes continuous DNA synthesis - Hashimoto, Yoshitami; Ray Chaudhuri, Arnab; Lopes, Massimo; Costanzo, Vincenzo (Nature structural & molecular biology, 2010)
Rad51 plays a central role in homologous recombination pathways. Now work with Xenopus laevis egg extracts shows that Rad51 prevents formation of DNA gaps at or behind replication forks, which are dependent on Mre11 nuclease activity. The role of Rad51 in an unperturbed cell cycle has been difficult to distinguish from its DNA repair function. Here, using EM to visualize replication intermediates assembled in Xenopus laevis egg extract, we show that Rad51 is required to prevent the accumulation of single-stranded DNA (ssDNA) gaps at replication forks and behind them. ssDNA gaps at forks arise from extended uncoupling of leading- and lagging-strand DNA synthesis. In contrast, ssDNA gaps behind forks, which are prevalent on damaged templates, result from Mre11-dependent degradation of newly synthesized DNA strands and are suppressed by inhibition of Mre11 nuclease activity. These findings reveal direct roles for Rad51 at replication forks, demonstrating that Rad51 protects newly synthesized DNA from Mre11-dependent degradation and promotes continuous DNA synthesis.